Wondrous One Sheet Origami - Mukerji, Meenakshi, 1962- (Milton : CRC Press LLC, 2019)
Wondrous One Sheet Origami is a how-to book full of beautiful origami designs covering a wide range of folding levels from simple to high intermediate, with more emphasis on the latter. The book is meant for audiences 12 years of age and above, and children folding at higher than age level. Most of the designs are flat and suitable for mounting on cards or framing as gifts. Features Richly illustrated full-color book with clear, crisp diagrams following international standard, and an abundance of photographs of finished models Select designs hand-picked by the author based on social media responses Most of the designs incorporate color-change, a technique showing both sides of paper for enhanced beauty "Meenakshi Mukerji's work is both intricate and lovely. She's greatly respected in the origami world, one of the well-known world leaders in modular origami. Her books offer a nice exposition of the mathematical elements, but you're not being hit over the head with math lessons. You learn things without even realizing that you have." -Dr. Robert J. Lang "Meenakshi Mukerji is one of today's masters of modular origami, designs comprised of multiple pieces of paper. She also brings her ingenuity and creativity to designs made from a single piece of paper. Among the most appealing aspects of her single sheet work is the way she subtly manipulates a purely geometric form to fold a flower, a leaf, a butterfly, or card suits." -Peter Engel
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: MATHEMATICS / General; MATHEMATICS / Recreations & Games; MATHEMATICS / Functional Analysis; Origami